The undesired : a thriller - Yrsa Sigurðardóttir (Minotaur Books, 2017)
"Aldis hates her job working in a juvenile detention center in rural Iceland. The boys are difficult, the owners are unpleasant, and there are mysterious noises at night. And then two of the boys go astray. Decades later, single father Odinn is looking into alleged abuse at the center. The more he finds out, though, the more it seems the odd events of the 1970s are linked to the accident that killed his ex-wife. Was her death something more sinister? Yrsa Sigurdardottir is a huge European bestseller both with her crime and horror novels. You might want to sleep with the light on after reading The Undesired. "--